Effect of Poly-Herbal Mixture and Butyric Acid on the Cleansing of the Uterus and Resumption of Ovarian Cyclicity in Murrah Buffaloes - Chandra, Subhash; Oberoi, Parminder Singh; Singh, Man; Kumar, Chandan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present experiment was conducted to evaluate the effect of a poly-herbal mixture and butyric acid supplementation, alone and in combination, on uterine cleansing of buffaloes during the transition period. Thirty-six Murrah buffaloes were selected 30 days before parturition and randomly divided into four equal groups with nine animals in each. The control group (T0) animals were fed diet as per farm feeding practice. Treatment groups T1, T2 and T3 were supplemented with poly-herbal mixture alone (T1), poly-herbal mixture + 200 ml butyric acid (T2) and with 200 ml butyric acid alone (T3) respectively. Postpartum involution of the uterus and cervix, fluid in the uterus, and ovarian follicular status were assessed by transrectal ultrasonography on the 7th, 14th, 21st, and 28th days. The blood samples were collected by jugular venipuncture into heparinized tubes from day 7 to day 42 postpartum; plasma was separated and stored under -200C until analyzed for progesterone estimation. The rate of uterine and cervical involution was significantly (p< 0.05) higher in supplemented groups compared to the control group. The proportion of buffaloes with large ovarian follicles within 28 days postpartum was also significantly (p< 0.05) higher in the treatment group compared to the control group. Plasma progesterone levels on day 35 postpartum in buffaloes under T1 and T2 group increased significantly (p<0.05) over the control group. The poly-herbal mixture facilitated early involution of the cervix and uterus, efficient cleansing of lochia, and improved subsequent fertility. It has potential to be used in dairy animals for improving postpartum reproductive efficiency.